Front Cover Picture: Site‐Selective Rhodium(III)‐Catalyzed C−H Amination of 7‐Azaindoles with Anthranils: Synthesis and Anticancer Evaluation (Adv. Synth. Catal. 20/2017). Issue 20 (6th September 2017) - Jeon, Mijin; Park, Jihye; Dey, Prasanta; Oh, Yongguk; Oh, Hyunjung; Han, Sangil; Um, Sung Hee; Kim, Hyung Sik; Mishra, Neeraj Kumar; Kim, In Su
Abstract : Thefront cover picture, provided by Kim, Mishra and co‐workers, illustrates the synthetic strategy for the formation of ortho ‐aminated N ‐aryl‐7‐azaindoles based on the rhodium(III)‐ or iridium(III)‐catalyzed C−H functionalization using anthranils and azides. The synthesized 7‐azaindoles were readily transformed into biologically relevant azaindoloacridines, azaindoloacridones, and bis‐indoles. Notably, all synthetic products were evaluated for anticancer activity against human breast adenocarcinoma cells, human renal carcinoma cells, and human prostate adenocarcinoma cells. Some of 7‐azaindole derivatives displayed potent cytotoxicity competitive with anticancer doxorubicin. Details can be found in the communication on pages 3471–3478 (M. Jeon, J. Park, P. Dey, Y. Oh, H. Oh, S. Han, S. H. Um, H. S. Kim, N. K. Mishra, I. S. Kim, Adv. Synth. Catal .2017, 359, 3471–3478; DOI10.1002/adsc.201700800 ).